The PERSonalized Glucose Optimization Through Nutritional Intervention (PERSON) Study: Rationale, Design and Preliminary Screening Results - Gijbels, Anouk; Trouwborst, Inez; Jardon, Kelly M.; Hul, Gabby B.; Siebelink, Els; Bowser, Suzanne M.; Yildiz, Dilemin; Wanders, Lisa; Erdos, Balázs; Thijssen, Dick H. J.; Feskens, Edith J. M.; Goossens, Gijs H.; et al. (Frontiers in Nutrition, 2021)
It is well established that the etiology of type 2 diabetes differs between individuals. Insulin resistance (IR) may develop in different tissues, but the severity of IR may differ in key metabolic organs such as the liver and skeletal muscle. Recent evidence suggests that these distinct tissue-specific IR phenotypes may also respond differentially to dietary macronutrient composition with respect to improvements in glucose metabolism. The main objective of the PERSON study is to investigate the effects of an optimal versus sub-optimal dietary macronutrient intervention according to tissue-specific IR phenotype on glucose metabolism and other health outcomes. In total, 240 overweight/obese (BMI 25-40 kg/m2) men and women (age 40-75y) with either skeletal muscle insulin resistance (MIR) or hepatic insulin resistance (LIR) will participate in a two-center, randomized, double-blind, parallel, 12-week dietary intervention study. At screening, participants undergo a 7-point oral glucose tolerance test (OGTT) to determine the hepatic insulin resistance index (HIRI) and muscle insulin sensitivity index (MISI), classifying each participant as either ‘No MIR/LIR’, ‘MIR’, ‘LIR’, or ‘combined MIR/LIR’. Individuals with MIR or LIR are randomized to follow one of two isocaloric diets varying in macronutrient content and quality, that is hypothesized to be either an optimal or suboptimal diet, depending on their tissue-specific IR phenotype (MIR/LIR). Extensive measurements in a controlled laboratory setting as well as phenotyping in daily life are performed before and after the intervention. The primary study outcome is the difference in change in disposition index, which is the product of insulin sensitivity and first-phase insulin secretion, between participants who received their hypothesized optimal or suboptimal diet. The PERSON study is one of the first randomized clinical trials in the field of precision nutrition to test effects of a more personalized dietary intervention based on IR phenotype. The results of the PERSON study will contribute knowledge on the effectiveness of targeted nutritional strategies to the emerging field of precision nutrition, and improve our understanding of the complex pathophysiology of whole body and tissue-specific IR. This trial is registered at clinicaltrials.gov as NCT03708419 (https://clinicaltrials.gov/ct2/show/NCT03708419).